Kenali Tipe Media Sosialmu : Pelatihan Promosi Produk UMKM Bagi Siswa SMK TPI Gedangan Sidoarjo - Endra Rahmawati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
SMK TPI Gedangan Sidoarjo is one of the private high schools in Sidoarjo that offers 3 expertise programs, namely Mechanical Engineering, Automotive Light Vehicle Engineering, and Software Engineering (RPL). These programs are designed to equip students with practical skills that are in accordance with the needs of industry and the world of work. With the vision of the school is to produce middle-class workers who are ready to enter society, industry, and become independent entrepreneurs, have a global perspective, have noble character, and can apply themselves. On the other hand, many vocational schools have not provided systematic guidance or practical curriculum on the use of various types of social media for business promotion purposes. In order to improve the quality of students, 28 students were sent to learn about how to promote MSME products through social media. This training aims to explore how vocational schools can effectively utilize social media to promote their MSME products by recognizing the differences in characteristics and functions of each platform. With this approach, patterns of social media usage that are right on target can be found as well as training or mentoring strategies that are in accordance with student needs. The results of this training can be a reference for developing relevant and applicable digital marketing learning modules in the vocational high school environment. The results of participant feedback at the end of the training showed that 91% of students could understand the material provided and the trainer could provide effective UMKM product promotion solutions according to the current needs of students.